Novel benzonitrile-based AIE host with high triplet energy for highly efficient solution-processed blue TADF OLEDs. (February 2023) - Jiang, Wei; Zhang, Guanghao; Zhao, Guimin; Wang, Xinjian; Tian, Wenwen; Sun, Yueming
Abstract: Developing high-performance host materials for blue thermally activated delayed fluorescence organic light-emitting diodes (TADF-OLEDs) is an effective way to improve emission efficiency through overcoming intermolecular interactions. In this work, three novel AIE-active materials with twisted donor-acceptor structures (3phCN-Cz, 3phCN-ICz and 3phCN-tCzICz) are designed and synthesized by modifying the donor unit. Encouragingly, all the molecules exhibited high triplet energies (>2.80 eV) to prevent exciton returning and aggregation‐induced emission (AIE) property for suppressing exciton quenching. Furthermore, systematic studies demonstrated that 3phCN-ICz and 3phCN-tCzICz with larger steric resistance units can not only possess good thermal and electrochemical stability but also exhibit excellent inhibition ability of intermolecular interactions, which are suitable for constructing high-efficiency solution-processed blue TADF devices. Ultimately, the 4TCzBN was employed as the blue TADF emitter, and the solution-processed OLEDs based on 3phCN-ICz achieved the maximum external quantum efficiency (EQEmax ), the maximum current efficiency (CEmax ), and the lowest turn-on voltage of 22.04%, 41.88 cd A −1, and 3.5 V, respectively. This work demonstrates the potential application of AIE materials with high triplet energy for solution-processed blue TADF OLEDs. Graphical abstract: Image 1 Highlights: Three novel AIE-active materials with high triplet energy levels (>2.80 eV) were obtained. The intermolecular interactions of these compounds have been effectively inhibited. The solution-processed blue TADF-OLEDs achieved a EQEmax and the lowest Von of 22.04% and 3.5 V, respectively.